Attaining high electrical conductivity and toughness in PA6 by combined addition of MWCNT and rubber - González, Imanol; Eguiazábal, José Ignacio; Nazabal, Jon (Composites. Part A, Applied science and manufacturing, 2012)
Tough polyamide 6 (PA6)/multi-walled carbon nanotube (MWCNT) nanocomposites modified by a maleated styrene/ethylene–butylene/styrene (mSEBS) were obtained in the melt state. The resistance calculations showed that both the conductivity values and the percolation threshold was not consequence of the physical contact among the nanotubes, and a double percolation phenomenon was observed after rubber addition. The addition of rubber did not affect the dispersion of the nanotubes, but the presence of MWCNT decreased the rubber particle size due to an increase in viscosity. Besides a high electrical conductivity and an elastic modulus similar to that of the PA6, the joint presence of 5% in weight (wt.%) MWCNT and 20wt.% mSEBS was able to provide both a large impact strength and clear ductile behaviour. The matrix yielding of the carbon nanotube-based nanocomposites was less extensive than in nanoclay-based composites. However, they were efficient enough to lead to a clear multi-functionality.